Piltdown, realism, and public trust in 1950s England - Mackay, M (Johns Hopkins University Press, 2022)
Opening with the 1953 exposure of the Piltdown hoax, and its surprisingly extensive and irreverent media reception, this essay argues that public trust in national institutions was among the pressing concerns of English culture throughout the 1950s, and a recurrent theme of its major realist fiction. Focusing on novels by Kingsley Amis, C. P. Snow, and Angus Wilson about fraud and forgery in institutional settings, the essay proposes that questions of motivated misrepresentation allowed novelists to emphasize partiality and prejudice in historical and literary narrative in ways that anticipated the reflexivity of both modes later in the century.